Prolonged learning and hasty stopping: The Wald problem with ambiguity - Sarah Auster; Yeon-Koo Che; Konrad Mierendorff (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
This paper studies sequential information acquisition by an ambiguity-averse decision maker (DM), who decides how long to collect information before taking an irreversible action. The agent optimizes against the worst-case belief and updates prior by prior. We show that the consideration of ambiguity gives rise to rich dynamics: compared to the Bayesian DM, the DM here tends to experiment excessively when facing modest uncertainty and, to counteract it, may stop experimenting prematurely when facing high uncertainty. In the latter case, the DM's stopping rule is non-monotonic in beliefs and features randomized stopping.
Keywords: C61; D81; D83; D91; 330; Wald problem; ambiguity aversion; prolonged learning; preemptive stopping